Mesenchymal stem cells in the treatment of diabetes mellitus: perspectives - Olga Ulyanova; Temirlan Karibekov; Galiya Shaimardanova; Larissa Kozina (National Scientific Medical Center, 2018)
Over recent decades, diabetes mellitus remains one of the main public healthcare problems worldwide with a tendency to steady growth. Actual prevalence of only type 2 diabetes mellitus among adults (20-79 years old) in Kazakhstan was higher than it was expected and amounted to 8.2% according to the Kazakh epidemiological study NOMAD. Diabetes mellitus is a major risk factor for ischemic heart disease and stroke, which collectively account for high rates of morbidity and mortality among adult patients. Transplantation of mesenchymal stem cells was considered to be the most promising treatment approach for diabetes mellitus.